Elastoplastic deformation of rotating disk made of aluminum dispersion-hardened alloys - Matvienko, Oleg V.; Daneyko, Olga I.; Valikhov, Vladimir; Platov, Vladimir V.; Zhukov, Ilya A.; Vorozhtsov, Alexander B. (Metals)
This paper studies the plastic deformation of a rotating disk made of aluminum dispersion-hardened alloys using mechanical tensile tests and a structured study using optical microscopy methods. Alloys such as AA5056 and A356 with dispersed Al3Er and TiB2 particles are used as the initial materials. Tensile strength testing of the obtained alloys shows that the addition of Al3Er particles in the AA5056 alloy composition leads to an increase in its ultimate stress limit (USL) and plasticity from 170 to 204 MPa and from 14.7 to 21%, respectively, although the modifying effect is not observed during crystallization. The addition of TiB2 particles to the A356 alloy composition also leads to a simultaneous increase in the yield strength, USL, and plasticity from 102 to 145 MPa, from 204 to 263 MPa, and from 2.3 to 2.8%, respectively. The study of the stress-strain state of the disk was carried out in the framework of deformed solid mechanics. The equilibrium equations were integrated analytically, taking into account the hardening conditions obtained from the experimental investigations. This made it possible to write the analytical relations for the radial and circumferential stresses and to determine the conditions of plastic deformation and loss of strength. The plastic resistance of a disk depends on the ratio between its outer and inner radii. The plastic resistance decreases with increasing disk width at a constant inner radius, which is associated with a stronger effect from the centrifugal force field. At a higher rotational rate of narrow disks, the tangential stresses are high and can exceed the USL value. A356 and A356-TiB2 alloys are more brittle than the AA5056 and AA5056-Al3Er alloys. In the case of wide rotating disks, AA5056 and AA5056-Al3Er alloys are preferable.